APPROACH TO DEVELOPING A MARITIME CYBERSECURITY VIRTUAL TRAINING ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The maritime industry is increasingly reliant on digital systems for navigation, communication, cargo management, and other critical functions. As these systems become more interconnected and technologically advanced, they also become vulnerable to cyber threats. A virtual training environment allows maritime personnel to simulate cyber attacks and practice responding to them, enhancing their preparedness and resilience against real-world cyber threats. Cyber attacks targeting maritime assets can have severe consequences, including disruptions to operations, financial losses, environmental damage, and even threats to human safety. By providing virtual training environments, maritime organizations can identify and mitigate cybersecurity risks before they escalate into actual incidents, thereby safeguarding their assets and operations. Regulatory bodies, such as the International Maritime Organization (IMO) and various national maritime authorities, have established guidelines and regulations aimed at enhancing cybersecurity in the maritime sector. Developing a virtual training environment enables maritime organizations to ensure compliance with these regulations by training personnel on cybersecurity best practices and regulatory requirements. Conducting hands-on cybersecurity training in a real-world maritime environment can be logistically challenging and costly. A virtual training environment offers a cost-effective alternative by allowing personnel to engage in realistic cybersecurity scenarios without the need for physical equipment or resources. This paper presents an approach to developing a maritime cybersecurity virtual training environment utilizing open-source software.